2019
DOI: 10.21082/ijas.v20n1.2019.p19-28
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Indonesian Shallots Based on Bulb-Tunic Patterns and Morphological Characters

Abstract: <p class="abstrakinggris"><span class="tlid-translation">Variation within bulb tunics has been used to determine the genetic diversity in <em>Allium</em> species, including shallots</span><span class="tlid-translation"><span>. </span></span>However, no such study has been reported for shallots of Indonesia. The study aimed to analyze the genetic diversity of the Indonesian shallots based on the bulb-tunic patterns. Thirty-five shallot genotypes from main pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Moreover, as micro-mineral bodies, calcium oxalate crystals will be formed only as specific crystal types with morphologies characteristic of a particular species. Herlina et al (2019) reported that calcium oxalate crystals control morphology, which is regulated by the cells and genetics. This suggests that based on the presence of crystals, it is possible to separate individual species as well as identify different plant species (Zhang et al 2014;Grechana et al 2020).…”
Section: Stemmentioning
confidence: 99%
“…Moreover, as micro-mineral bodies, calcium oxalate crystals will be formed only as specific crystal types with morphologies characteristic of a particular species. Herlina et al (2019) reported that calcium oxalate crystals control morphology, which is regulated by the cells and genetics. This suggests that based on the presence of crystals, it is possible to separate individual species as well as identify different plant species (Zhang et al 2014;Grechana et al 2020).…”
Section: Stemmentioning
confidence: 99%
“…Penampilan tanaman berbeda pada kondisi iklim yang bervariasi dan varietas dari spesies yang sama yang dibudidayakan di lingkungan yang sama memberikan hasil yang berbeda karena potensi tanaman tergantung pada interaksi genetik dan lingkungan (Visalakshi et al, 2018) Informasi mengenai keragaman genetik dan heritabilitas bawang merah di Indonesia masih sangat terbatas. Hasil penelitian mengenai keragaman genetik dan heritabilitas sudah dilakukan pada bawang merah, di Indonesia oleh Herlina et al (2019); dan Herlina et al (2018); di Ethiophia oleh Degewione et al (2011); dan bawang bombay (Allium cepa L.) di India oleh Solanki et al (2015), dan Dangi et al (2018). Oleh karena itu perlu dilakukan penelitian mengenai keragaman genetik dan heritabilitas bawang merah.…”
Section: Pendahuluanunclassified
“…Shallot's important value in Indonesia is proven yearly with consumption increases [7] and price fluctuations [8]. Shallot production reaches 7.21% of the total vegetable produced in Indonesia, ranking third after cabbage and potatoes.…”
Section: Introductionmentioning
confidence: 99%